Evaluation of wheat and emmer varieties for artisanal baking, pasta making, and sensory quality. (March 2017) - Kissing Kucek, Lisa; Dyck, Elizabeth; Russell, June; Clark, Liz; Hamelman, Jeffrey; Burns-Leader, Sharon; Senders, Stefan; Jones, Jenny; Benscher, David; Davis, Michael; Roth, Greg; Zwinger, Steve; et al.
Abstract: Identifying varieties best suited to local food systems requires a comprehensive understanding of varietal performance from field to fork. After conducting four years of field trials to test which varieties of ancient, heritage, and modern wheat grow best on organically managed land, we screened a subset of varieties for bread, pastry, pasta, and cooked grain quality. The varieties evaluated were three lines of emmer ( T. turgidum L. ssp. dicoccum Schrank ex Schübl) and eleven lines of common wheat ( Triticum aestivum L.), including two modern soft wheat varieties, four soft heritage wheat varieties, four hard modern wheat varieties, and one hard heritage wheat variety. A diverse group of bakers, chefs, researchers, and consumers compared varieties for qualities of interest to regional markets. Participants assessed differences in sensory profiles, pasta making ability, and baking quality for sourdough, matzah crackers, yeast bread, and shortbread cookies. In addition to detecting significant differences among varieties for pasta, sourdough, and pastry quality, participants documented variation in texture and flavor for the evaluated products. By demonstrating which varieties perform best in the field, in the bakery, and on our taste buds, these results can support recommendations that strengthen the revival of local grain economies. Highlights: Varieties differ in sourdough, yeast bread, matzot, pasta, and shortbread quality. Studied soft heritage wheat varieties had low to moderate baking quality. Wheat varieties demonstrated unique visual, textural, and flavor descriptions. Sensory attributes of varieties often change depending what product is evaluated. Unbalanced designs may improve the efficiency of sensory evaluation.